Hypoxia Stimulates SUMOylation-Dependent Stabilization of KDM5B - Zhou, Bingluo; Zhu, Yiran; Xu, Wenxia; Zhou, Qiyin; Tan, Linghui; Zhu, Liyuan; Chen, Hui; Feng, Lifeng; Hou, Tianlun; Wang, Xian; Chen, Dingwei; Jin, Hongchuan (Frontiers in Cell and Developmental Biology, 2021)
Hypoxia is an important characteristic of the tumor microenvironment. Tumor cells can survive and propagate under the hypoxia stress through activating a series of adaption response. Herein, we found that lysine-specific demethylase 5B (KDM5B) was upregulated in gastric cancer (GC) under hypoxia condition. The genetic knockdown or chemical inhibition of KDM5B impaired the growth of GC cell adapted to hypoxia. Interestingly, the upregulation of KDM5B in hypoxia response was associated with the SUMOylation of KDM5B. SUMOylation stabilized KDM5B protein by reducing the competitive modification of ubiquitination. Furthermore, protein inhibitor of activated STAT 4 (PIAS4) was determined as the SUMO E3 ligase showing increased interaction with KDM5B under hypoxia condition. Inhibition of KDM5B caused significant downregulation of hypoxia-inducible factor-1α (HIF-1α) protein and target genes under hypoxia. As a result, co-targeting KDM5B significantly improved the anti-tumor efficacy of antiangiogenic therapy in vivo. Taken together, PIAS4 mediated SUMOylation stabilized KDM5B protein through disturbing ubiquitination-dependent proteasomal degradation to overcome hypoxia stress. Targeting SUMOylation-dependent KDM5B upregulation might be considered when antiangiogenic therapy was applied in cancer treatment.